Effects of an isotonic beverage on autonomic regulation during and after exercise - Moreno Isadora Lessa; Pastre Carlos Marcelo; Ferreira Celso; de Abreu Luiz Carlos; Valenti Vitor Engrácia; Vanderlei Luiz Carlos Marques (Taylor & Francis Group, 2013)
Abstract Background With prolonged physical activity, it is important to maintain adequate fluid balance. The impact of consuming isotonic drinks during and after exercise on the autonomic regulation of cardiac function is unclear. This study aimed to analyze the effects of consuming an isotonic drink on heart rate variability (HRV) during and after prolonged exercise. Methods Thirty-one young males (21.55 ± 1.89 yr) performed three different protocols (48 h interval between each stage): I) maximal exercise test to determine the load for the protocols; II) Control protocol (CP) and; III). Experimental protocol (EP). The protocols consisted of 10 min at rest with the subject in the supine position, 90 min of treadmill exercise (60% of VO2 peak) and 60 min of rest placed in the dorsal decubitus position. No rehydration beverage consumption was allowed during CP. During EP, however, the subjects were given an isotonic solution (Gatorade, Brazil) containing carbohydrate (30 g), sodium (225 mg), chloride (210 mg) and potassium (60 mg) per 500 ml of the drink. For analysis of HRV data, time and frequency domain indices were investigated. HRV was recorded at rest (5-10 min), during exercise (25-30 min, 55-60 min and 85-90 min) and post-exercise (5-10 min, 15-20 min, 25-30 min, 40-45 min and 55-60 min). Results Regardless of hydration, alterations in the SNS and PSNS were observed, revealing an increase in the former and a decrease in the latter. Hydrating with isotonic solution during recovery induced significant changes in cardiac autonomic modulation, promoting faster recovery of linear HRV indices. Conclusion Hydration with isotonic solution did not significantly influence HRV during exercise; however, after exercise it promoted faster recovery of linear indices.